EXPLORING THE ROLE OF STAKEHOLDERS IN DAVELOPING TANJUNG BAYANG BEACH, MAKASSAR CITY - Eunike Eunike (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This research aims to analyze the role of stakeholders in managing Tanjung Bayang Beach, to identify the level of collaboration and cooperation among stakeholder elements, and to examine the challenges and opportunities in implementing the stakeholder model at this tourist attraction. The study employed a descriptive qualitative approach. Data were collected through in-depth interviews, direct field observations, and supporting documentation. The data were then thematically analyzed to illustrate the involvement, synergy, and role dynamics of various stakeholders, namely the government, local communities, business actors, academics, and the media, supporting tourism destination development. The findings reveal that each stakeholder has played a relatively effective role. The government focuses on providing regulations and developing infrastructure, and local communities are involved through tourism awareness groups. Business actors contribute by offering services and tourism activities, academics support through research and training, while the media plays a role in promoting and building the attraction’s image. The overall cooperation level among these parties is generally positive; however, several weaknesses persist, including limited coordination, funding constraints, and inadequate environmental awareness among some visitors. Furthermore, the research identified several challenges that require attention, including potential conflicts of interest, limited resources, and weak engagement management discipline. Despite these challenges, considerable opportunities exist, such as local economic development, human resource capacity building, and the utilization of information technology for promotion and destination management. Based on these findings, it can be concluded that the success of developing Tanjung Bayang Beach is strongly influenced by inclusive and adaptive cross-sector synergy. Therefore, this study recommends strengthening communication among stakeholders, enhancing stakeholder capacity, and implementing sustainable financing mechanisms. If these efforts are realized, Tanjung Bayang Beach has the potential to develop into a sustainable marine tourism attraction that not only contributes to the local economy but also preserves the coastal environment.